La escuela austriaca de economía: Una nota introductoria (2009)
The Austrian School of Economic Thought has its roots in the work of Carl Menger (1840-1921), who developed the basic principles of marginal analysis in order to explain, from a subjective perspective, the value of goods. This text presents, in a brief manner, some of Merger’s seminal ideas and some of the further developments that his followers have given to them.